Macroporous beads for lipase immobilization: kinetic resolution of a racemic drug intermediate - Bhushan, Indu; Parshad, Rajinder; Qazi, G. N.; Ingavle, Ganesh C.; Jamalpure, Trupti M.; Rajan, C. R.; Ponrathnam, Surendra; Gupta, V. K. (Journal of Bioactive and Compatible Polymers, 2007)
{Lipase isolated from Arthrobacter sp. (RRLJ-1, MTCC No. 5125, named ABL), is effective in resolving a wide range of racemic drug intermediates. In this study, ABL was immobilized on a series of synthetic macroporous epoxy copolymers beads with varying pore sizes, surface area and hydrophobicity. Poly(glycidyl methacrylate-co-ethylene dimethacrylate) beads, with 75% crosslink density and 10% of epoxy groups modified with dibutyl amine [
Keywords: auxin pulse; coco-peat; grape; micropropagation; plantlet survival